Pharmacokinetic mechanisms underlying clinical cases of valproic acid autoinduction: A review - Narjis Mhaimeed; Nada Mhaimeed; Mujeeb U. Shad (Journal of Affective Disorders Reports, 2022)
Although enzyme induction by valproic acid (VPA) has been documented in several case reports, clinical reports of VPA autoinduction are rare. In contrast, other antiepileptic drugs (AED) and/or mood stabilizers, such as carbamazepine and phenytoin, are well-documented to increase other drugs' metabolism as well as their own. This review analyzes data from published case reports of VPA autoinduction to elucidate plausible mechanisms underlying VPA autoinduction to enhance clinicians' awareness of VPA autoinduction and its management. A literature search using the following search terms: (('valproic acid' OR 'valproate' OR 'VPA') AND ('autoinduction' OR 'auto-induction' OR 'induction' OR 'inducibility')) revealed 14 records. However, only three papers described clinical cases of VPA autoinduction, with one research paper investigating the role of β-oxidation in VPA autoinduction without a clinical case description. As shown in Table 1, VPA autoinduction in case 1 was primarily formulation-based, cases 2–4 were dose-related, and case 5 involved protein displacement reaction with co-prescribed ibuprofen. All reviewed cases were Caucasian males, with a mean age (SD) of 44.0 ± 14.88, receiving a VPA formulation with different diagnoses, including bipolar disorder, schizophrenia, tuberous sclerosis, and traumatic brain injury. All VPA levels were trough levels obtained at the steady-state and analyzed by the same laboratories for each case. This review utilizes clinical data from a few published cases to present the complexities of pharmacokinetic mechanisms underlying VPA autoinduction. Nevertheless, clinicians should consider requesting free fraction along with the total VPA levels to diagnose and manage VPA autoinduction, particularly in clinically challenging patients.